Production and Marketing System Design at Artificial Insemination Centre (BBIB: Balai Besar Inseminasi Buatan) Singosari - Lutfi Diana Sari (Jurnal VOK@SINDO, 2013)
Information system of production and marketing is a system designed to ease and optimize the processing of production and marketing data in order to give useful information for employees as well as customers in a company. This system is created by using SQL Server data base and C# programming language. This application can only be accessed by employees at BBIB Singosari who have been registered in the system. The information given in this system is based on the users’ needs. Thus, users in each department would get information data based on their own login. By using this system, users are able to get information needed more easily and effectively.